Village Social Welfare in the Village Building Program of the TVRI East Java Public Broadcasting Institution 2021-2023 - Mohammad Hasan Fauzi; Dimas Prakoso Nugroho (Prodi Ilmu Komunikasi UTM, 2025)
Village social welfare is an organized field of activities carried out either by the village administration or the private sector which has the main objective of fulfilling basic needs, improving the quality of life of village communities, as well as increasing village independence and overcoming social problems. This study attempts to analyze how village social welfare is described in the program